Analysis of particulate size distribution and concentrations from simulated jet engine bleed air incidents - Mann, Garrett W.; Eckels, Steven J.; Jones, Byron W. (My University, 2015)
Engine oil migrating into the bleed air stream of aircraft environmental control systems occurs with enough frequency and deleterious effects to generate significant public interest. While previous work has explored the chemical makeup of the contaminants in the aircraft cabin during these events, little is known about the characteristics of the aerosol resulting from oil contamination of bleed air. This paper presents particle counter data (giving both size distributions and concentration information) of the oil droplets from simulated jet engine bleed air. Four particle counters—a scanning mobility analyzer, an aerodynamic particle-sizer, an optical particle counter, and a water-based condensation particle counter—were used in the study encompassing a size range from 13nm to 20μm. The aerosol characterization is given for different bleed air temperatures and pressures. The data show a substantial increase of ultra-fine particles as the temperature is increased to the maximum temperatures expected during normal aircraft operation. This increase in ultra-fine particles is consistent with smoke generated from the oil. The pressure of the bleed air had little discernible effect on the particle-size and concentration.
Keywords: Jet engine bleed air; Engine oil; Particle counters